Systematic Literature Review: Peran Kepala Sekolah dalam Membangun Budaya Baca melalui Gerakan Literasi di Sekolah - Hariyani Prasetyaningtyas; Nurhattati Nurhattati; Kamaludin Kamaludin (Journal on Education, 2025)
The development of a reading culture closest to children is in the school environment. The school principal is one of the drivers in developing a reading culture in the school environment. As the leader of a school institution, he has a very strategic role in developing a reading culture in the school. Reading culture is a process that must be empowered through sensitive and conscious efforts from the time the child is born. The culture of reading contributes to a person's complete intellectual and emotional development, so that individuals are able to develop themselves and realize their potential. Thinking is followed by a reading-writing process which will ultimately lead to critical thinking, problem solving, the development of knowledge, and the creation of a work